Relevance of portfolio effects in adopting sustainable farming practices. (1st September 2021) - Weltin, Meike; Zasada, Ingo; Hüttel, Silke
Abstract: The concept of sustainable intensification (SI) unifies ecologically and socially sustainable agricultural practises while preserving economically viable farm businesses. To fully exploit their ecological advantages, smart mixes of SI measures at both the farm and local scale are required. This paper investigates farmers' adoption decisions using a mixed-methods approach for the northern German Plain. Based on focus group discussion, we first identify the study region's relevant SI measures. Using an existing data set, we then quantitatively assess the complementarity of the locally relevant measures using a multivariate probit model. Finally, we use a path modelling approach to explore how the perceived economic and environmental benefits of farmers' applied measures relate to their intentions to broaden their SI portfolios through complementary practices. We find support for complementary use of measures and positive reinforcements of current and intended use of measures. We conclude that such paths are relevant for analysing adoption behaviour. Such expanded and contextualised behavioural approaches are necessary to develop intervention schemes for upscaling sustainable farming practices. Highlights: We analyse farmers' adoption behaviour of sustainable intensification practices. We select a regional portfolio of sustainable practices using qualitative data. Farm survey data allow exploring complementary use of the portfolios' practices. Experiences of the used portfolio affect farmers' intentions to use more practices. We offer an explorative base to integrate portfolio effects in adoption models.